(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Sudden death is said to be sudden or unexpected when the victim not known to have been suffering from any dangerous disease, injury or poisoning is found dead or dies within 24 hours after the onset of terminal illness (WHO). Incidences of sudden natural deaths are increasing now a days and specifically in healthy young individuals can arise suspicion of foul play. Our study may help to provide epidemiological data regarding the sudden death that can be used to control disease outbreaks, identifying emerging causes or changes in disease pattern so that appropriate action can be taken to reduce the morbidity and mortality. The present study undertaken to find the socio-demographic profile (age, sex and religion etc.) of the deceased of sudden death. This prospective study had been conducted on autopsy cases brought to tertiary health center of Vadodara, Central Gujarat for the period of one year. During study period total 2240 autopsies were conducted, of which 224 cases (10%) were sudden deaths. Most of the cases were from the 41 - 50 years age group. Of the 224 cases, 149 were due to diseases of cardiovascular system and 63 due to diseases of respiratory system. We observed that sudden death cases were higher in young age group and cardiovascular system was most commonly involved.